KEPEMIMPINAN EFEKTIF KEPALA SEKOLAH DALAM MENGEMBANGKAN PROFESIONALISME GURU - Anizah, Anizah; Maretta, Winda Fitri (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
Education is able to support future development while education could develop the potential of learners in facing global competition. In the educational world, the teachersâ professionalism is needed in order to gain a qualified output. To achieve this goal, principals are very influential in developing teachersâ professionalism. Related to the problem, the purpose of this paper was to know the principals strategy in developing teachersâ professionalism. The method used in this research was qualitative. To develop the teachersâ professionalism, the principal did organize a portfolio assessment system in the context of teacherâs certification preparation to obtain an certificate educator through Professional Persistence (PKP) in the form of Classroom Action Research (PTK). The expected results, it can develop the teachersâ professionalism in managing the teaching and learning process.Â Keywords: Effective Leadership, Principal, Teachersâ Professionalism.